Penerapan Media Tangga Satuan Panjang terhadap Hasil Belajar Siswa - Dewantari, Sabbihisma Maydita; Mabruroh, Naily Al; Nurwahidah, Seviatin; Maulidin, M Aldiyan; Khasanah, Linaria Arofatul Ilmi Uswatun (Lembaga Yasin AlSys, 2023)
Mathematics is one of the subjects that students consider difficult. This happens because students do not know how to operate multiplication and division, especially in the matter of measuring units of length. In addition, students consider mathematics lessons to be boring, since the teacher uses only the lecture method. This study aims to find out how the application of unit ladder media to student learning outcomes. This type of research is a classroom action research conducted for one month at SD Muhammadiyah Sidoharjo Lamongan with material on measuring length using standard units in grade IV students totaling 22 students, with 10 men and 12 women and carried out in II cycles. Cycle I showed an average score of 66.13 and with a learning completion of 66%. While in cycle II the average score of students is 80 with a learning completion of 80%. Based on the research conducted, it can be concluded that the use of learning media for length units in length measurement materials using standard units can improve student learning outcomes.